THE DEALING IN THE ART GALLERIES: HOW IS AFFECTING THE CONTEMPORARY ART WORLD - Iolanda-Georgiana ANASTASIEI (Studia Universitatis Babeș-Bolyai. Philosophia)
The Dealing in the Art Galleries: How is Affecting the Contemporary Art World. The present study focuses on the different types of artist-gallery collaborations established in the contemporary art world, trying to underline the impact that such collaborations can have on the art world in general. I shall point several effects that these types of collaborations can have in relation to the art market or even in relation to the aesthetics of contemporary art. The role of private art collectors is also of some importance in this equation and I shall also focus on some relevant examples of galleries or art dealers symptomatic to some of the issues discussed.